”Vi har redan tillräckligt med judar här”.Tonsättaren Hans Holewa och exilens dubbelhet - Rosengren, Henrik (Nordisk judaistik/Scandinavian Jewish Studies, 2016)
Tonsättaren, radiomedarbetaren och musikern Hans Holewa (1905–1991) anlände till Sverige 1937 som landsflyktig undan den tilltagande antisemitismen i Wien, drygt ett halvår innan Österrike annekterades av Nazityskland. Som invandrad radikal tonsättare med den så kallade tolvtonstekniken som utgångspunkt, med judiskt påbrå och med engagemang inom vänsterrörelsen kom Holewas svenska exiltillvaro utgöra ett spänningsfält med många dimensioner. Följande artikel tar utgångspunkt i två aspekter kopplade till Holewas exiltillvaro, dels Holewa som representant för en radikal musikestetik, dels hans relation till det judiska. Framställningen kretsar kring frågor om hur Holewa mottogs i det svenska musiklivet i relation till hans estetiska förhållningssätt och hur hans situation kan förstås med utgångspunkt i termen ”exilens dubbelhet”. En tredje frågeställning berör vilken betydelse den judiska kulturen hade för hans exiltillvaro och tonsättarskap. * * *‘We already have enough Jews here’: composer Hans Holewa and the doubleness of exile • The composer and musician Hans Holewa (1905–1991) arrived in Sweden in 1937 after fleeing from the Nazi-influenced Austria. The following article focus on two aspects linked to Holewas exile; Holewa as a representative of a radical musical aesthetics, and his relationship to his Jewish background. The article revolves around the question of how Holewa was received in the Swedish music life in relation to his aesthetic approach and how his situation in exile can be understood by reference to the term ‘exile duality’. A third issue concerns the significance of his Jewish loyalty during exile and in his composing. The article shows how the exile could serve both as an interruption, for example in relation to his Jewish loyalty and compositional technique, but also as an expression of continuity as he was a bearer of a modern aesthetic attitude which he formulated in Austria but which had higher relevance in his Swedish exile, however, not without some opposition from the Swedish music establishment. ""